Seminal vesicle metastasis of cutaneous malignant melanoma: An unusual and challenging presentation - Foahom Kamwa, Alain D. (Can Urol Assoc J, 2015)
Malignant melanoma is a tumour, which usually involves skin melanocytes. Involvement of the male genitourinary (GU) system by melanoma is an uncommon and challenging diagnosis. We report the first case of seminal vesicle metastasis from a primary cutaneous melanoma in a 58-year-old man, with hemospermia as the only clinical sign. This case highlights the role of multiparametric magnetic resonance imaging, as a more sensitive assessment to early detect metastatic melanoma in the GU system. The patient underwent a robot-assisted laparoscopic bilateral seminal vesiculectomy, which had good functional and oncological results and is still in complete remission at the 1-year follow-up.